LITERATURE REVIEW: THE EFFECT OF EDUCATION ON ECONOMIC GROWTH IN CENTRAL JAVA - Mukaromah Syakoer (ID Solutions, 2022)
A country can be said to be fair and prosperous is to carry out economic development. Investment in education is not only beneficial for individuals, but also for the general public and the country. It is well known that Central Java has made progress in the field of education. This can be seen from the School Participation Rate (APS) data which has increased from 2018 to 2020. This study uses a literature review technique with a descriptive qualitative approach. Literature review is a scientific survey on a particular topic. The survey is conducted by searching and analyzing literature such as scientific articles, books, theses and others. The findings of this study are that there are many studies that link education and the economy, where education affects economic growth. But on the other hand, there are several supporting factors in increasing economic growth, including capital expenditures, inflation, and PAD. Education is not only obtained formally but can also be obtained from non-formal education to improve abilities and skills for the community. This has an effect on increasing a productive workforce so that economic growth is more optimal.